An investigation into the effectiveness of using securitization as a means of financing low-cost housing - Dube, Lloyd (My University, 2008)
This dissertation offers an in-depth study of the use of mortgage-backed securitization to finance low-cost housing. Although mortgage-backed securitization has been used successfully to finance residential property in the higher end of the market, private investors have shown little or no interest in exploiting the R68 billion low-cost housing market through securitization. The descriptive survey method was used. This included a literature review of the changes that need to be made in the legal and institutional framework in order to attract private investors into the low-cost housing securitization market. The survey indicated that for securitization to succeed in the low-cost housing sector, the government needs to form low-cost housing development partnerships with banks and developers. In addition to the partnerships, the government needs to minimize credit risk by guaranteeing low-cost housing securities and to develop economic infrastructure in the townships that will result in the creation of jobs. Most institutions favored incentives such as tax breaks and higher returns on the securities issued by low-cost housing special purpose vehicles.